Perspektif Al-Qur’an Tentang Tipologi Anak Dan Cara Menyikapinya: Sebuah Kajian Tafsir Tematik - Mahmud, Basri; Jamaluddin, Jamaluddin; Mujahid, Mujahid (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2025)
This research aims to uncover the meaning of "child" and its typology from the perspective of the Qur'an. This study is descriptive qualitative in nature and employs the thematic interpretation method. The data used consists of primary data in the form of Qur'anic verses and secondary data related to this topic. The data is processed through a series of steps including reduction, data presentation, and verification until a conclusion is reached. The research findings show that the terminology for "child" in the Qur'an appears in various forms. For instance, the word zurriyyah is mentioned 32 times, walad 62 times, ghulam 13 times, al-Sabiy 2 times, al-Tiflu 4 times, al-Bintu and its variants are mentioned 17 times, and ibn along with its derivatives appears 112 times. The word walad has a broader meaning as it encompasses all types of children, unlike the word ibn, which also means "child" but is specifically used to refer to a male child, while a female child is referred to as ibnah. The word ghulam focuses on a child who has reached maturity, al-sabiy refers to a child who has not yet reached puberty, while al-tifl refers to a child younger than one called al-Sabiy. As for the typology of children from the Qur'anic perspective, children can be an obstacle or an enemy if they prevent someone from doing good deeds. They are also described as ornaments of the world, meant to be a means for parents to perform righteous acts. Additionally, children are a test from Allah to examine how parents treat them. On the other hand, righteous children who are obedient to Allah and devoted to their parents bring comfort and peace to the heart.